An integrative adoption model of video-based learning. Issue 4 (1st August 2016) - Mikalef, Patrick; Pappas, Ilias O.; Giannakos, Michail
Abstract : Purpose: Video-Based Learning (VBL) is gaining increasing attention as an educational means in settings such as the flipped classroom and massive open online courses (MOOCs). The value of VBL has been recognized in a range of contexts due to the ability to extend opportunities for life-long education for all socio-economic levels, removing geographical boundaries while at the same time alleviating time constraints. Yet, despite the advantages featured by VBL and some promising early outcomes regarding its effectiveness, little is known about what influences individuals to adopt VBL systems and technologies Design/methodology/approach: Building on behavioral and adoption-acceptance theories as well as on past empirical studies on e-learning, a conceptual model of VBL adoption is proposed. By analyzing survey data from 260 VBL learners, the conceptual model is put to test by means of Structural Equation Modeling (SEM Findings: Outcomes indicate that performance expectancy and computer self-efficacy have a positive direct effect on behavioral intention to adopt VBL. In addition, effort expectancy and social influence positively impact performance expectancy, while computer self-efficacy is found to enhance effort expectancy and perceived behavioral control. Originality/value: This study integrates several theoretical perspectives that are applied to adoption of novel Information Technologies and in addition builds on findings of past empirical research on learning technologies. In effect, the conceptual model along with outcomes provide an integrative perspective of adoption determinants.